Implementation of MLC 2006 for Indonesian Seafarers: A Gap Analysis in Aspects of Health Care and Social Security of Seafarers on Board - Budi Purnomo; Imam Fachruddin; Antoni Arif Priadi; Damoyanto Purba; April Gunawan (Institut Teknologi Sepuluh Nopember, 2020)
Maritime workers are workers who are regulated internationally through the Maritime Labour Convention (MLC) 2006 which has been ratified by the Indonesian government through Law No. 15 of 2016. In the convention regulated aspects include health care on ships and land, social security, welfare facilities on land, access to seafarers' complaints, protection of health and safety, and accident prevention. This study aims to evaluate the application of the convention so far through the gap analysis method and index performance analysis (IPA). Gap analysis is used to get the difference between the performances and expectations of the respondents. To see the variables that need to be improved, maintained, not a priority for improvement or variables that are above expectation then used the IPA model. This research examines how seafarers' performances and expectations are related to the implementation of MLC in Indonesia, especially in the aspects of health care, social security, and welfare on board. The results show that almost all research variables suggest a gap although relatively small in value. First, it can be summarized that there are several variables that need to be improved such as Protection and health care, Hospitals on board, and complaints. These variable variables need to get attention for future improvements. There are several variables that need to be maintained such as visit a doctor, health, sick, disability, opportunity to use telephone and internet access, procedures for handling complaints, occupational health and safety (OHS), risk assessment, and safety meetings. Last, variables that are considered excessive in implementation should also get the attention that is medical